Decision Support System for the Most Chosen and Preferred Smartphone Using the MOORA Method: Author's Country: Indonesia (Buana Information Technology and Computer Sciences (BIT and CS), 2025)
The rapid development of the digital era in Indonesia has posed difficulties for consumers in choosing the right smartphone for them. This research aims to develop a DSS (Decision Support System) using the MOORA (Multi-Objective Optimization on the Basis of Ratio Analysis) method to determine the best smartphone according to consumer preferences, with criteria including smartphone price, design, usability flexibility, durability, performance, and camera quality. Evaluation is carried out by calculating the weight value of each criterion and ranking the smartphone alternatives based on a questionnaire. The research results show that the MOORA method is able to determine the best smartphone according to the people of Solo and help consumers choose the right smartphone for them. This research involves five of the most widely used smartphones in Indonesia (Apple, Samsung, Xiaomi, Oppo, Vivo, and Infinix) using the MOORA (Multi-Objective Optimization on the Basis of Ratio Analysis) method based on the defined criteria. The results show that Xiaomi smartphones rank first both in terms of quality and user quantity. The practical implications of this research are significant, providing consumers with a data-driven approach to make informed smartphone choices, thereby enhancing their purchasing satisfaction